ANALISIS TINJAUAN BIBLIOMETRIK PADA LITERATUR SISTEM MONETER ISLAM (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2023)
Research on the Islamic Monetary System is an important concern that contributes to the development of Islamic economics and finance. The large amount of literature related to Islamic economics and finance motivates researchers to discover new and different things. So an insightful study of bibliometric literature helps to understand the patterns and directions of research regarding the Islamic monetary system. This research collected 153 articles from the Scopus database for the period 1970 to 2023. Applications used included Microsoft Excel and VOSviewer to describe graphic data, citation analysis, co-occurrence analysis, and content analysis. The results of the analysis reveal the countries that published articles, the distribution of research over the research time interval, the most influential authors in the field of Islamic finance, the most cited journals, and keywords that frequently appear. There are five research streams identified, including (1) monetary policy transmission mechanisms through sharia financial channels, (2) Islamic monetary policy instruments in several OIC countries, (3) currency concepts and encouraging the economy from an Islamic perspective, (4) sector stability finance according to the views of Islamic science and finance, (5) interdependence in Islamic financial markets and linkages with conventional financial markets and macroeconomic variables. This research can address gaps in research in the field of Islamic Monetary Systems and offer further research for Islamic economics and finance researchers. Penelitian Sistem Moneter Islam menjadi perhatian penting yang berkontribusi pada pengembangan keilmuan ekonomi dan keuangan Islam. Banyaknya literatur terkait ekonomi dan dan keuangan Islam, memotivasi para peneliti untuk menemukan hal yang baru dan berbeda. Maka kajian tinjauan literatur bibliometrik membantu untuk memahami pola dan arah penelitian mengenai sistem moneter Islam. Penelitian ini mengumpulkan 153 artikel dari basis data Scopus untuk periode 1970 hingga 2023. Aplikasi yang digunakan antara lain Microsoft Excel dan VOSviewer untuk menggambarkan grafik data, analisis kutipan, analisis co-occurrence, dan analisis analisis isi. Hasil analisis mengungkap negara-negara yang menerbitkan artikel, sebaran penelitian pada interval waktu penelitian, penulis yang paling berpengaruh bidang moneter Islam, jurnal yang paling banyak dikutip, serta kata kunci yang sering muncul. Terdapat lima arus penelitian yang teridentifikasi antara lain (1) mekanisme transmisi kebijakan moneter melalui jalur keuangan syariah, (2) instrumen kebijakan moneter Islam di beberapa negara OKI, (3) konsep mata uang dan perannya pada perekonomian dalam perspektif Islam, (4) stabilitas sektor keuangan menurut dalam pandangan ilmu dan keuangan islam, (5) interdependensi dalam pasar keuangan syariah dan keterkaitan dengan pasar keuangan konvensional serta variabel makroekonomi. Penelitian ini dapat mengatasi kesenjangan dalam penelitian di bidang Sistem Moneter Islam dan menawarkan penelitian selanjutnya bagi para peneliti ekonomi dan keuangan Islam.